NAL1 forms a molecular cage to regulate FZP phase separation - Ling-Yun Huang; Ting-Ting Wang; Peng-Tao Shi; Ze-Yu Song; Wei-Fei Chen; Na-Nv Liu; Xia Ai; Hai-Hong Li; Xi-Miao Hou; Li-Bing Wang; Kun-Ming Chen; Stephane Rety; et al. (Proceedings of the National Academy of Sciences, 2025)
NARROW LEAF 1 ( NAL1 ), originally identified for its role in shaping leaf morphology, plant architecture, and various agronomic traits in rice, has remained enigmatic in terms of the molecular mechanisms governing its multifaceted functions. In this study, we present a comprehensive structural analysis of NAL1 proteins, shedding light on how NAL1 regulates the phase separation of its physiological substrate, FRIZZY PANICLE (FZP), a transcription factor. We determined that NAL1 assembles as a hexamer and forms a molecular cage with a wide central channel and three narrower lateral channels, which could discriminate its different substrates into the catalytic sites. Most notably, our investigation unveils that FZP readily forms molecular condensates via phase separation both in vitro and in vivo. NAL1 fine-tunes FZP condensation, maintaining optimal concentrations to enhance transcriptional activity. While phase separation roles include sequestration and suppression of transcriptional or enzymatic activity, our study highlights its context-dependent contribution to transcriptional regulation. NAL1 assumes a pivotal role in regulating the states of these molecular condensates through its proteolytic activity, subsequently enhancing transcriptional cascades. Our findings offer insights into comprehending the molecular mechanisms underpinning NAL1’s diverse functions, with far-reaching implications for the field of plant biology. Additionally, these insights provide valuable guidance for the development of rational breeding strategies aimed at enhancing crop productivity.